Interacting hands: the role of attention for the joint Simon effect - Liepelt, Roman (Frontiers in Psychology, 2014)
Recent research in monkeys and humans has shown that the presence of the hands near an object enhances spatial processing for objects presented near the hand. This study aimed to test the effect of hand position on the joint Simon effect. In Experiment 1, two human co-actors shared a Simon task while placing their response hands either near the objects appearing on the monitor or away from the monitor. Experiment 2 varied each co-actor’s hand position independently. Experiment 3 tested whether enhanced spatial processing for objects presented near the hand is obtained when replacing one of the two co-actors by a non-human event-producing rubber hand. Experiment 1 provided evidence for a Simon effect. Hand position significantly modulated the size of the Simon effect in the joint Simon task showing an increased Simon effect when the hands of both actors were located near the objects on the monitor, than when they were located away from the monitor. Experiment 2 replicated this finding showing an increased Simon effect when the actor’s hand was located near the objects on the monitor, but only when the co-actor also produced action events in spatial reference. A similar hand position effect was observed in Experiment 3 when a non-human rubber hand replaced the human co-actor. These findings suggest that external action events that are produced in spatial reference bias the distribution of attention to the area near the hand. This strengthens the weight of the spatial response codes (referential coding) and hence increases the joint Simon effect.